Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3748/wjg.v13.i9.1372
|View full text |Cite
|
Sign up to set email alerts
|

Using computed tomography scans to develop an бex-vivo�� gastric model

Abstract: The objective of this research was to use abdominal computed tomography (CT) scans to non-invasively quantify anthropometrical data of the human stomach and to concomitantly create an anatomically correct and distensible ex-vivo gastric model. Thirty-three abdominal CT scans of human subjects were obtained and were imported into reconstruction software to generate 3D models of the stomachs. Anthropometrical data such as gastric wall thickness, gastric surface area and gastric volume were subsequently quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Burgos et al compared the size and volume of bariatric surgery patients' stomachs to autopsy specimens of normal controls and found no difference between the two groups [11]. This is further supported by Henry et al who showed no difference in gastric thickness in those with BMI>25 to those with BMI<25 [4]. The results of the present study suggest that no significant correlation exists between gastric wall thickness and body mass index.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Burgos et al compared the size and volume of bariatric surgery patients' stomachs to autopsy specimens of normal controls and found no difference between the two groups [11]. This is further supported by Henry et al who showed no difference in gastric thickness in those with BMI>25 to those with BMI<25 [4]. The results of the present study suggest that no significant correlation exists between gastric wall thickness and body mass index.…”
Section: Discussionsupporting
confidence: 81%
“…CT evaluation of the thickness of the gastric wall demonstrated an average thickness of 5.0 mm in the antrum of the stomach and 2.0 mm at the anterior wall of the gastric body [3]. More recently, Henry et al [4] used CT imaging with 3D reconstruction of images to compare the thickness of the gastric wall in those with normal BMI (17-25) to those with high BMI (25-40). Mean gastric wall thickness varied between 2.35 mm and 5.43 mm with no significant difference found between the two groups.…”
Section: Introductionmentioning
confidence: 97%
“…The proportion of papers presented on medical modelling fell in comparison to those focussed on direct implant production or XCT inspection and metrology, but a large number of studies furthered research during this time, a selection of which can be seen in references [1,[37][38][39][40][41][42][43][44]. This period showed a prevalence of the use of XCT in the design of various implants, summarised in a paper that detailed recent advances in production of tissue-engineering scaffolds [45].…”
Section: History 2005-2010mentioning
confidence: 99%
“…This thickness was an average value derived from the literatures. 12,13 The wall was then divided into five layers to represent the alternating smooth muscle and layers of interstitial cells of Cajal (ICC). A high resolution trilinear finite element mesh was then embedded within the elements of the geometric mesh 9,16 to create computational points at the element vertices.…”
Section: Model Construction and Methods For Simulationmentioning
confidence: 99%
“…As mentioned previously, this figure was obtained as average value derived from the literatures. The thickness of human stomachs in vivo has been examined by Henry et al 12 and Huh et al 13 For measurements, they used CT and endoscopic ultrasound, respectively, and five or six points were selected at each of multiple transverse slices of the stomach. From their data, they determined the total stomach wall thickness to be 2.35-5.43 mm.…”
Section: Effect Of Thickness On Stomach Wallmentioning
confidence: 99%